Formulation of Oil-in-Water Cream from Mangosteen (Garcinia mangostana L.) Pericarp Extract Preserved by Gamma Irradiation - E. Isabella; T. Pohan (Atom Indonesia, 2013)
The aim of this researchwas to formulate mangosteen (Garcinia mangostana L.) pericarp extract into oil-in-water (O/W) cream which stable and durable. In order to improve the shelf life durability of the formula, the irradiation of formula using gamma rays from cobalt-60 was done. The concentrations of extract were varied to 1, 2 and 3% and were irradiated by gamma rays with doses of 5, 7.5 and 10 kGy. Physicochemical and microbiological properties of these formulas were carried outfor 90 days stored at 30 ± 2°C and 40 ± 2°C. It was found that both of physicochemical and microbiological properties of the formulas were changed by extract concentrations and after irradiation. The irradiated formulas with dose up to 7.5 kGy, which were stored at 30 ± 2°C and 40 ± 2°C, presented acceptable physicochemical and microbiological stability for at least 90 days. Analysis by TLC (Thin Layer Chromatography)-densitometry to study decomposition of G. mangostana pericarp extract cream formulas was carried out 24 h after preparation and 90 day after storage. The result of TLC-densitometry analysis showed that G. mangostana pericarp extract in the cream formulas did not develope significant decomposition after 90 days of storage. Decontamination dose for all formulas was found to be about 7.5 kGy. At this condition, the bacteria and mold-yeast have been killed, without reducing the antioxidant activity.Received: 24 November 2013; Revised: 20 December 2013; Accepted: 26 December 2013